PbCap380, a novel oocyst capsule protein, is essential for malaria parasite survival in the mosquito - Srinivasan, Prakash (2008)
An essential requisite for transmission of Plasmodium, the causative agent of malaria, is the successful completion of a complex developmental cycle in its mosquito vector. Of hundreds of ookinetes that form in the mosquito midgut, only few transform into oocysts, a loss attributed to the action of the mosquito immune system. However, once oocysts form, they appear to be resistant to mosquito defences. During oocyst development, a thick capsule forms around the parasite and appears to function as a protective cover. Little information is available about the composition of this capsule. Here we report on the identification and partial characterization of the first Plasmodium oocyst capsule protein (PbCap380). Genetic analysis indicates that the gene is essential and that PbCap380(−) mutant parasites form oocysts in normal numbers but are gradually eliminated. As a result, mosquitoes infected with PbCap380(−) parasites do not transmit malaria. Targeting of the oocyst capsule may provide a new strategy for malaria control.